Dissolution of hydrogen in metals and casting alloys - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2022)
Thermodynamic calculations have shown that hydrogen from atmospheric water vapors can penetrate aluminum, iron and copper, especially into their melts. Hydrogen atoms in these metals are in free and adsorbed states. Strong and dense oxide films on the surfaces of aluminum, iron and copper significantly reduce the solubility of hydrogen in these metals. Copper and iron nanocrystals more actively adsorb atomic hydrogen than aluminum nanocrystals. This is one of the main reasons for the weak solubility of hydrogen in aluminum and the large desorption of hydrogen atoms in the crystallization of aluminum compared to iron and copper.